Metabonomic analysis of the protective effect of quercetin on the toxicity induced by mixture of organophosphate pesticides in rat urine. (May 2017) - Qi, L; Cao, C; Hu, L; Chen, S; Zhao, X; Sun, C
The present study aims to investigate the protective effect of quercetin against the joint toxic action induced by the mixture of four organophosphate pesticides (mixture-OPs) (dimethoate, acephate, dichlorvos, and phorate) at their corresponding no observed adverse effect level (NOAEL) using metabonomics. Rats were randomly divided into control, quercetin-treated, mixture-OPs-treated, and quercetin plus mixture-OPs-treated groups. Mixture-OPs and quercetin were given to the rats daily through drinking water and intragastric administration, respectively, for 90 days. The metabonomic profiles of rat urine were analyzed using ultra-performance liquid chromatography–mass spectrometry (UPLC/MS). The 14 metabolites significantly changed in the treatment groups compared with the control group, including the biomarkers of OPs exposure (dimethylphosphate, dimethyldithiophosphate, diethylphosphate) and the metabolites of quercetin (quercetin and isorhamnetina). The intensities of gentisic acid, creatinine, suberic acid, hippuric acid, uric acid, and citric acid significantly decreased, whereas the intensities of 7-methylguanine, estrone sulfate, and cholic acid significantly increased, in the mixture-OPs-treated group compared with the control group ( p < 0.01). The variation tendency of the aforementioned metabolites was significantly ameliorated in the high-dose quercetin (50 mg/(kg bw day)) plus mixture-OPs-treated group compared with the mixture-OPs-treated group ( p < 0.05). However, the intensities of these metabolites in the high-dose quercetin plus mixture-OPs-treated group were still significantly different from those of the control group ( p < 0.05). Results indicated that high dose of quercetin elicits a partial protective effect on the toxicity induced by mixture-OPs, including fatty acid and energy metabolism, antioxidant defense system, DNA damage, and liver and kidney function.